(untitled) (American Journal of Interdisciplinary Research and Development, 2024)
Bronchial asthma is a chronic inflammatory disorder of the airways that often coexists with other allergic diseases. The clinical manifestations and disease course of asthma can be significantly influenced by the climatic conditions of the region. This study aimed to investigate the features and progression of bronchial asthma in combination with other allergic diseases, with a particular focus on the impact of climatic factors.